Aspects of dealing with non-Muslims through Yusuf Al-Qaradawi’s book “Halal and Haram in Islam” An analytical descriptive study - Katih, Ismaie (Al-HIKMAH Journal, 2021)
This research aims to study the book Halal and Haram in Islam; To extrapolate the aspects of dealing with non-Muslims from it, and to achieve its set goals, the researcher followed the descriptive analytical approach, to discuss the problematic of the subject. Alcohol to non-Muslims, the manufacture of statues and crosses, the marriage of female writers, and how to deal with polytheistic parents, and that what is meant by dealing with non-Muslims is the exchange of benefits and public behavior related to extrapolation of coexistence and social development, in light of the contribution of both sides.